Bauran Pemasaran Komoditi Pakcoy Hijau Organik Di PT. Orgo Organic Farm Indonesia - Sania Fitria Rahmah; Nitriana Kridha Kirana; Adelia Kharisma Putri Raharjo; Prasmita Dian Wijayati (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
PT Orgo Organic Farm Indonesia, located in Malang City, is a company specializing in organic vegetable production. To cope with increasing competition in the market, PT Orgo Organic Farm Indonesia needs to establish the right marketing mix strategy to boost sales. The aim of this journal article is to identify the company's internal and external conditions and analyze the marketing mix strategy implemented. The method used to describe internal and external conditions and analyze the marketing mix is descriptive method. Based on the analysis, it can be concluded that: (1) The external and internal conditions of PT Orgo Organic Farm Indonesia highlight the advantages of organic vegetable products with various benefits, but also indicate shortcomings such as incomplete product packaging, less intensive promotion, and suboptimal transportation infrastructure. (2) The marketing mix strategy implemented to increase product sales includes focusing on production development with emphasis on quantity, quality, and continuity (3K), developing the